Efficacy and Safety of Xelox in Comparison with Folfox in Metastatic Colorectal Cancer - Tooba Imtiaz Baqai, Ghulam Haider, Nargis Aalam Abro, Berkha Rani, Reeta Kumari, Javeria Anzar, Kiran Abbas (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The study aimed to evaluate efficacy and safety of Xelox in comparison to Folfox chemotherapy for metastatic colorectal cancer. Methods: A quasi experimental study was undertaken at the Department of Oncology, Jinnah Postgraduate Medical Center between April 2022 to November 2022. All the patients coming to oncology department JPMC with confirmed diagnosis of metastatic colorectal cancer of age 18 years and above were included. All data were recorded in a predefined proforma by the researchers. Patients’ age, gender, and comorbidity, family history, and clinical characteristics were noted. The primary endpoints were the overall response rates and the frequency of adverse effects. Results: A total of 200 patients were enrolled with a mean age of 40 ± 14.38 years. There were 100 participants in the Xelox group while 100 participants in the Folfox group. About 45 (45%) in the Xelox group and 62 (62%) in the Folfox group reported adverse effects of the chemotherapy (p=0.015). The rate of neutropenia grade III/IV was greater in the Folfox category than the Xelox. Hand foot syndrome was significantly more frequently reported in the Xelox group than the Folfox group 22 (48.89%) and 18 (29.03%); p=0.036, respectively. Oral mucositis was also more frequently reported in patients taking Xelox than Folfox [20 (44.44%) vs. 15 (24.19%); p=0.023]. There was no significant statistical difference between Xelox and Folfox in terms of patient overall response rates. Conclusion: According to the study, there are no appreciable differences between Xelox and Folfox chemotherapy in terms of overall response rates among patients with colorectal cancer. However, overall, patients taking Folfox reported significantly higher rates of adverse effects with the exception of hand foot syndrome and oral mucositis which was more frequent in the Xelox group. Keywords: colorectal carcinoma, chemotherapy, xelox, folfox, Capecitabine, Oxaliplatin, fluorouracil